Two-color laser absorption near 5 μm for temperature and nitric oxide sensing in high-temperature gases. (December 2017) - Almodovar, Christopher A.; Spearrin, R. Mitchell; Hanson, Ronald K.
Abstract: An infrared laser-absorption technique for in situ temperature and nitric oxide species sensing in high-temperature gases is presented. A pair of quantum cascade lasers in the mid-infrared near 5 μm were utilized to probe rovibrational transitions in nitric oxide's fundamental band. The line parameters of the selected transitions, including line strengths and collision broadening coefficients of nitric oxide with argon and nitrogen, were evaluated during controlled room-temperature static cell experiments and high-temperature shock tube experiments at temperatures between 1000 and 3000 K, and pressures between 1 and 5 atm. These studies provided new insights into the temperature dependence of nitric oxide collision broadening, highlighting the inadequacies of the power law over a broad temperature range. With an accurate spectroscopic model over a broad temperature range, the quantitative two-color temperature sensing strategy was demonstrated in non-reactive shock tube experiments from 1000 to 3000 K to validate thermometry and during a nitric oxide formation experiment near 1700 K and 4 atm to highlight capability for temporally-resolved species measurements at MHz rates. The technique has applicability for sensing in a broad range of flow fields that involve high-temperature air. Abstract : Highlights: New laser absorption method for temperature sensing in non-equilibrium air. New data for 2γ NO−N2 and 2γ NOAr at high temperatures. Improved uncertainty of measured spectroscopic parameters. 2γNO−N2 power-law temperature dependence breaks down outside of temperature range.